Analisis Faktor Aktifitas Fisik Resiko Terjadi Hemoroid Di Klinik Etika - Sunarto Sunarto (Poltekkes Kemenkes Surakarta, 2016)
Abstract : Hemorrhoids, Physical Activity Factor, Risk Occurrence of Hemorrhoids. Hemorrhoids are known in the community as hemorrhoids or piles is a common disease and has been there since time immemorial. The incidence of hemorrhoids tend to increase with age person, where the peak age is 45-65 tahun.Hemoroid found in 50% of people above 50 years. Hemorrhoids can be suffered by both men and women. Physical activity is one of the risk factors of hemorrhoids, but this type of activity is different from the order to each person. Formulation of the problem :Does the physical activity that has the risk of hemorrhoids in etika clinical. The purpose of this study was To determine physical activity has the risk of hemorrhoids in etika clinical. This research is observational analytic with cross sectional method. Samples are 29 respondents who are hemorrhoids sufferers who carry out checks in etika clinical ngemplak boyolali. The determination of the study respondents with accidental. The statistical test was preceded classical assumption test then multiple linear regression analysis. The results of this study were (1) Physical activity mostly sitting is a risk factor occurrence of hemorrhoids with a great risk of 0.37%, (2) Less physical activity is a risk factor of hemorrhoids with great risk of 0.33%, (3) Activities physical frequent straining when BAB is a risk factor of hemorrhoids with great risk 0.63%., (4) physical activity often carry heavy loads is a risk factor of hemorrhoids with great risk of 0.26%.. This research is simultaneously student activity within the organization and emotional intelligence related learning motivation the III level of students DIV Nursing Health Polytechnic of Surakarta.